Curve Analysis After Bracing in Scoliosis Patients - Rury Tiara Oktariza; Indriyani Indriyani; Ecian Nada Utami; Erwin Maulana (Sriwijaya Journal of Medicine, 2024)
Bracing is one of the scoliosis treatment methods recommended for patients with a curve of 25° to 40° still growing child or with curves less than 25°. Bracing aims to prevent the progression of curvature. This study aimed to evaluate the decrease in the Cobb angle after a 3-month bracing in scoliosis patients. We retrospectively reviewed the medical records of 67 scoliosis patients for age, gender, and the Cobb angle before and after wearing a brace for 3 months. The data was analyzed using a paired t-test with a confidence level of 95%. The research results showed that scoliosis is predominant in females (76.12%) and at 10-15 years old (60.78%). The mean pre-brace Cobb angle of 24.94° (±7.24) was reduced significantly (P < 0.001) to 16.37° (±7.34). The use of a brace in scoliosis patients, especially teenagers, can correct the curvature of the spine.